Differential responses of adiposity, inflammation and autonomic function to aerobic versus resistance training in older adults - Flavia A C Wanderley (2013)
Background: Increased body fat, autonomic dysfunction and low-grade chronic inflammation are interrelated risk factors implicated in the etiology of several chronic conditions normally presented by older adults. Objective: This study aims to assess the effectiveness of different training protocols on reducing body fat, improving autonomic function, and decreasing low-grade systemic inflammation in community-dwelling elderly adults. Methods: Fifty participants (11 men, 68 +/- 5.5 years) were randomly allocated into resistance or aerobic training or control groups. Evaluations were done at baseline and following the 8-month intervention period on their body composition (assessed by DXA), inflammatory biomarkers (high-sensitivity C-reactive protein [hs-CRP], tumor necrosis-alpha [TNF-alpha], interferon-gamma [IFN-gamma], interleukins-6 and -10 [IL-6, IL-10]), lipoproteic profile, fasting glycemia, blood pressure, heart rate variability (HRV; frequency and time domains) and aerobic fitness (assessed by six-minute walk distance [6MWD]). A paired t-test was used to detect changes (%Delta=[(post-test score - pretest score)/pre-test score] x100) within groups, while between-group differences were analyzed using the one-way ANOVA or General Linear Models. Results: A significant change (Delta%) both in total (-5.4 +/- 6.3% and -3.3 +/- 2.9%, respectively) and central body fat (8.9 +/- 11.3% and -4.8 +/- 4.5%) was observed in resistance and aerobic training groups, respectively; along with a change in resting systolic and diastolic blood pressures (-9.2 +/- 9.8% and -8.5 +/- 9.6%), heart rate (-4.6 +/- 6.5%), hs-CRP (-18.6 +/- 60.6%), and 6MWD (9.5 +/- 6.9%) in response to aerobic training. Conclusions: The present findings provide further evidence for the benefits of aerobic and resistance training on reducing body fat. Aerobic training was demonstrated to reduce hs-CRP and blood pressure in community-dwelling elderly participants with no serious medical conditions.